Respiratory support and the process of weaning from invasive mechanical ventilation in patients admitted to the Adult ICU of a University Hospital: Descriptive longitudinal study (Research, Society and Development, 2024)
Objectives: To describe the profile of respiratory support and the process of weaning from invasive mechanical ventilation in patients admitted to the adult intensive care unit (ICU) of a university hospital and to comparatively evaluate the clinical outcomes of these patients in relation to the type of respiratory support used. Methodology: This was a descriptive longitudinal observational study of patients admitted to the hospital's Adult ICU between 10/16/2023 and 12/15/2023 and aged 18 years or older. Results: A homogeneous patient profile was found, with a predominance of overweight in both groups and an estimated higher risk of mortality in the intubated group. There was a predominance of patients admitted without ventilatory support, with low-flow oxygen therapy (FiO2